2019
DOI: 10.1609/aaai.v33i01.33012556
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transformation Method for Discriminant Analysis of Multi-Channel Resting State fMRI

Abstract: Analysis of resting state - functional Magnetic Resonance Imaging (rs-fMRI) data has been a challenging problem due to a high homogeneity, large intra-class variability, limited samples and difference in acquisition technologies/techniques. These issues are predominant in the case of Attention Deficit Hyperactivity Disorder (ADHD). In this paper, we propose a new Deep Transformation Method (DTM) that extracts the discriminant latent feature space from rsfMRI and projects it in the subsequent layer for classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The multi-modal joint learning CNN architecture was superior to CNNs using either data modality alone. Aradhya et al (2019) also used a CNN classifier and extracted features using the Deep Transformation Method (DTM).…”
Section: Discussion and Qualitative Reviewmentioning
confidence: 99%
“…The multi-modal joint learning CNN architecture was superior to CNNs using either data modality alone. Aradhya et al (2019) also used a CNN classifier and extracted features using the Deep Transformation Method (DTM).…”
Section: Discussion and Qualitative Reviewmentioning
confidence: 99%
“…The multi-modal joint learning CNN architecture was superior to CNNs using either data modality alone (Zou et al, 2017). Aradhya et al (2019) also used a CNN classifier and extracted features using the Deep Transformation Method (DTM).…”
Section: Discussion and Qualitative Reviewmentioning
confidence: 99%
“…They used 90 subregions in their study. Following the AAL template, Aradhya et al 32 used 90 brain subregions in the cerebrum. In their study, the brain network analysis demonstrated that the difference in functional activities is very high in the temporal lobe and posterior cingulate cortex (PCC), which implies inattentiveness and impulsivity in ADHD.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, instead of extracting features with tailored methods, the features were learned by data in the layers of deep learning networks. A deep transformation method (DTM) was used by Aradhya et al 32 This method extracted the discriminant latent feature space and projected it in the subsequent layer. Also, DTM utilized the convolutional layers to extract low‐level spatial features and transform them into high‐level features in their study.…”
Section: Methodsmentioning
confidence: 99%